Development of a Method for Obtaining Nanoscale Magnesium Carbonate Stabilized with Chitosan as the Basis of Scaffold Matrices for Regenerative Medicine - A. V. Blinov; Z. A. Rekhman; A. A. Gvozdenko; M. A. Yasnaya; M. A. Kolodkin; M. A. Taravanov (Advanced Engineering Research, 2024)
Introduction. In the public domain there is enough literature on methods of treating the musculoskeletal system. The possibilities of eliminating bone defects using patients' own (autologous) bones are described. The authors of theoretical and applied studies also suggest using synthetic bioinert materials made of polymers, calcium phosphates, plastics, and metals. The creation of three-dimensional matrices based on scaffolds for the formation of systems that are as close as possible to bone tissue in structure has been studied. It is known that the active substances of the scaffold matrix can be hydroxyapatite, tricalcium phosphate, as well as silicates, carbonates of magnesium, calcium, copper, zinc, and manganese. The issue requires detailed study. In light of the stated problem, the features of the listed materials should be considered separately. There are no such publications. The presented work is intended to fill this gap. Its objective is to create a synthesis method and study the properties of nanoscale magnesium carbonate.Materials and Methods. The materials for the study were samples of magnesium carbonate nanoparticles obtained by chemical precipitation in water. They were studied using X-ray diffractometry, scanning electron microscopy, infrared spectroscopy, and dynamic light scattering. Quantum-chemical modeling was performed using the QChem program and the IQmol molecular editor.Results. It has been established that magnesium carbonate particles are rod-shaped, 2 to 10 μm in length. They consist of nanoparticles from 30 to 60 nm. Quantum-chemical modeling has revealed the energy features of the interaction of the basic magnesium carbonate, firstly, with chitosan with carbonate, and secondly, with a separate chitosan molecule. In the first case, the energy value is lower, in the second, it is higher. This indicates the chemical and energetic advantage of forming such complexes. The corresponding indices for the optimal coordination of magnesium carbonate with chitosan have been determined. In this case, the interaction is provided by the hydroxyl group of chitosan attached to the C6 residue of glucosamine. For this process, the lowest energy ∆E=462.387 kcal/mol and chemical hardness η=0.062 eV are noted. Magnesium carbonate nanoparticles have optimal radius and zeta potential with the following parameters of the initial reagents: 0.018 mol of ammonium carbonate, 0.03 mol of magnesium acetate, 0.15 g of chitosan.Discussion and Conclusion. The obtained data indicate that nanoscale basic magnesium carbonate is a promising material with a wide range of possibilities of practical application. From this point of view, its role in metabolic processes, namely in the assimilation of macronutrients, is of particular interest. Nanoscale osteotropic magnesium micronutrient synthesized in a biopolymer environment can be used as a biologically active filler for three-dimensional scaffold matrices. Implementation of this solution in medical practice will improve the efficiency of bone tissue restoration.